The Impact of Human Resources Information Systems and Internal Control on Employee Performance at PT. Sinar Artha Universe - Amalia Khoirunnisa; Murniad Murniad; Dhea Zatir (Green Publisher Indonesia, 2025)
The purpose of this study is to determine the Impact of Human Resources Information System and Internal Control on Employee Performance at PT. The Universe Artha Rays partially or simultaneously. Using an associative method with a quantitative approach. Sampling was 83 people. Data collection techniques and tools are questionnaires or questionnaires. The data processing is assisted by Microsoft Excel and SPSS Software version 29. Based on the t_hitung value of 7,644 > t_tabel 1,663, the H_a was accepted with a sig of 0.04 < α 0.05 and a statistical F value of 40,084 > F of table 3,110 the decision was H_a accepted. The results of the study show 1.) Human Resources Information System has a positive and significant impact on Employee Performance; 2.) Internal Control has a positive and significant impact on Employee Performance; 3.) Human Resource Information System and Internal Control simultaneously have a positive and significant impact on Employee Performance. In addition, it has a contribution of 50.1% while the rest is influenced by other variables that are not studied.